Involvement of Manganese in Conversion of Phenylalanine to Benzaldehyde by Lactic Acid Bacteria - Nierop Groot, Masja N. (American Society for Microbiology, 1999)
We examined the involvement of Mn(II) in the conversion of phenylalanine to benzaldehyde in cell extracts of lactic acid bacteria. Experiments performed with Lactobacillus plantarum demonstrated that Mn(II), present at high levels in this strain, is involved in benzaldehyde formation by catalyzing the conversion of phenylpyruvic acid. Experiments performed with various lactic acid bacterial strains belonging to different genera revealed that benzaldehyde formation in a strain was related to a high Mn(II) level.